Grey area and delinquency in liquid fuel trading — tax dimension of a phenomenon - Ćwiąkała-Małys, Anna; Piotrowska, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
For many years one of the dominant source of a budget income has been indirect tax. The biggest part of it is constituted by tax on goods and services and excise tax. Inflows of excise tax generated from liquid fuel trade are exposed to reductions due to illegal production as well as trade in grey area. Specialized crime groups are involved in production and trade of fake fuel. Illegal practices are more and more differentiated and reach in their scope outside our country. Law enforcement agencies are involved in disclosing this illegal trade. Additionally, tax agencies are authorized to disclose illegal practices of fuel trade in grey area. All actions taken by authorised agencies are to secure State Treasury matter in guaranteeing financial security.
Keywords: szara strefa; zjawisko; wymiar podatkowy; handel paliwami